2015
DOI: 10.4049/jimmunol.1401414
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase–Mediated Activation of Glycogen Synthase Kinase 3β Regulates IL-33 Receptor Internalization and IL-33 Signaling

Abstract: IL-33, a relatively new member of the IL-1 cytokine family, plays a crucial role in allergic inflammation and acute lung injury. ST2L, the receptor for IL-33, is expressed on immune effector cells and lung epithelia, and plays a critical role in triggering inflammation. We have previously shown that ST2L stability is regulated by the ubiquitin-proteasome system, however its upstream internalization has not been studied. Here, we demonstrate that glycogen synthase kinase 3β (GSK3β) regulates ST2L internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…IL‐1R4 expression is also regulated at a protein level on the cell surface. In the absence of IL‐33 stimulation, IL‐1R4 is constantly turned over with a reported protein half‐life of about 5 hours . Upon binding of IL‐33 to IL‐1R4 and recruitment of IL‐1R3, the IL‐33 R complex is internalized.…”
Section: Focus On the Il‐1r Familymentioning
confidence: 99%
“…IL‐1R4 expression is also regulated at a protein level on the cell surface. In the absence of IL‐33 stimulation, IL‐1R4 is constantly turned over with a reported protein half‐life of about 5 hours . Upon binding of IL‐33 to IL‐1R4 and recruitment of IL‐1R3, the IL‐33 R complex is internalized.…”
Section: Focus On the Il‐1r Familymentioning
confidence: 99%
“…Once activated, GSK-3β binds to and phosphorylates ST2L resulting in the swift internalization of ST2L. Once internalized ST2L is polyubiquitinated by the E3 ubiquitin ligase FBXL19 and subsequently degraded by the proteasome [31]. As sST2 functions as a decoy receptor for IL-33 it negatively regulates ST2 signalling by sequestering IL-33 and has been shown to down regulate Th2 cell-mediated immunologic responses [32].…”
Section: Il-33/st2 Signallingmentioning
confidence: 99%
“…31 Glycogen synthase kinase 3β (GSK3β), a serine/threonine kinase, regulates ST2L internalization. 51 It has been shown that inhibition of GSK3β attenuated IL-33–induced cytokine release. 31 As a negative regulator of the IL-33/ST2 signaling pathway, TIR8 (also known as SIGIRR) dimerizes with ST2L and ultimately dampens the bioactivity of IL-33.…”
Section: St2mentioning
confidence: 99%
“…IL-33 triggers IL-8 and IL-6 release from PBMCs, pulmonary endothelial cells, and epithelial cells, 31,51,80,99 thus inducing neutrophil influx into alveolar spaces. The effect of IL-33 on cytokine production might be partly blocked by sST2 80 or downregulation of ST2L.…”
Section: Il-33/st2 In Alimentioning
confidence: 99%